Perancangan Sistem Informasi Bencana di Kabupaten Padang Pariaman - Elmawati Elmawati; Veni Wedyawati (Jurnal Pendidikan Teknologi Kejuruan, 2019)
Disasters not we can know quickly because of the damage going on that trouble getting precise information. Badan Penanggulangan Bencana Daerah Kabupaten Padang Pariaman often difficulty in process data disaster that is because there is no system quickly in process the data. With the information systems that web-based this can provide disaster victim management a quick and exact in convey information about disasters that happened to the areas Kabupaten Padang Pariaman. This system will be made in use of language programming PHP that is a programming language is open source.